ANALYSIS OF IMC AND THE PERFIL DERMATOGLÍFIC OF THE STUDENTS OF THE SUBSEQUENT TECHNICAL TEACHING OF IFPA (Fiep Bulletin - online, 2011)
This study is characterized as a descriptive study whose objective was to make her a BMI analysis and dermatoglyphic profile of pupils in subsequent IFPA. Focus aimed to identify the characteristics of BMI and dermatoglyphic profile of the students and to relate them. The study sample consisted of forty-two (N = 42) pupils in subsequent Federal Institute in relation to age have not established any criteria, because teaching is not following a pre-established and in relation to sex, we used It is both. The measurement instrument was used in a anmenese, protocol for measuring the BMI and dermatoglyphics of Midler and Cumins (1942), and the data were collected on the campus of Itaituba and Altamira / PA. As the result, the dermatoglyphic profile was most predominant (78.57%) with clips and features on BMI was characterized with some (52.38%) with abnormalities, the study was conducted between September-October 2010. From the results and using descriptive statistics, we get the following results: Dermatoglyphic characteristics of the students were 2.39% for A, 11.90% for W, 7.14% to 78.38% and LW for L. In BMI was featured in 14.29% underweight, 47.62% normal, 30.95% and 7.14% on weight obese. When does the summation of all sorts of abnormal BMI is the value of 52.38%, the relationship between BMI and higher prevalence Dermatoglyphic characterized clip that had a high rate of abnormality. We made a link between the characteristics of abnormal BMI and the profile of the clip and concluded that about 74% of the clips feature has a high rate of change in BMI.
Keywords: Dermatoglyphics; BMI and Subsequent Teaching